RESONANCE OF MESSAGES ABOUT ACADEMIC INTEGRITY: ANALYSIS OF PUBLIC RESPONSES TO VIDEO OF UI LECTURER EXPOSING DOCTORAL DEGREE SCAM - Syafika Ramadhani; Nurhakki; Muhammad Qadaruddin; Sulvinajayanti; Reynaldi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
This study analyzes message resonance and public response dynamics to the issue of academic integrity in a YouTube video titled “UI Lecturer Exposes Doctoral Degree Scam.” The study uses a quantitative descriptive approach with Social Network Analysis (SNA) combined with sentiment and toxicity analysis. A total of 1,200 comments were collected through web scraping techniques using Communalytic. The results show that neutral sentiment dominates public responses, followed by negative and positive sentiment in smaller proportions. Network visualization shows the formation of opinion clusters with a number of central actors playing a role in amplifying the discourse. Although emotional expressions appear, the level of toxicity is relatively low. These findings indicate that the issue of academic integrity resonates morally in the digital space, but is discussed in a relatively rational and discursive manner. This study contributes to the integration of message resonance theory and social network analysis in the context of Indonesian social media.